Global skeletal uptake of 99mTc-methylene diphosphonate (GSU) in patients affected by endocrine diseases: comparison with biochemical markers of bone turnover - Scillitani, A; Dicembrino, F; Chiodini, I; Minisola, S; Fusilli, S; Di Giorgio, A; Garrubba, M; D'Aloiso, L; Frusciante, V; Torlontano, M; Modoni, S; Trischitta, V; et al. (Osteoporosis international, 2002)
This study aimed to clinically validate the global skeletal uptake (GSU) of (99m)Tc-methylene diphosphonate ((99m)Tc-MDP), and to compare it with a marker of bone formation (i.e. serum osteocalcin or OC) and an index of bone resorption (i.e. urinary deoxypyridinoline or U-DPD) in different endocrine disorders affecting the skeleton. We studied 29 female patients with thyrotoxicosis (TT), 27 with primary hyperparathyroidism (PHPT), 16 with acromegaly (AC), 15 with Cushing's syndrome (CS), and altogether 110 healthy women matched for age, BMI and menstrual status. In all subjects total body digital scan images (TBDS) were acquired at 5 min and at 4 h after the administration of (99m)Tc-MDP; the whole body retention (WBR) of the tracer was measured by counting two identical sets of rectangular ROIs, and GSU was subsequently calculated by drawing an irregular ROI on 4 h TBDS images. Serum OC was assessed by IRMA and urinary DPD by fluorometric detection after reverse phase high pressure chromatography. In TT patients GSU (40.0 +/- 5.1 vs 36.5 +/- 4.8%), OC (19.1 +/- 11.8 vs 7.1 +/- 2.9 microg/l) and U-DPD (62.4 +/- 42.7 vs 19.5 +/- 5.3 pmol/pmol) were significantly ( p<0.01) higher than in controls. PHPT patients showed GSU (47.2 +/- 6.6 vs 37.8 +/- 5.3%), OC (38.6 +/- 40.9 vs 8.2 +/- 2.5 microg/l), and U-DPD (55.0 +/- 51.3 vs 21.9 +/- 6.1 pmol/pmol) values significantly ( p<0.001) higher than controls. In CS patients, GSU (39.6 +/- 6.4 vs 32.7 +/- 3.5%; p<0.01) and U-DPD (22.8 +/- 8.4 vs 16.5 +/- 2.7 pmol/pmol; p<0.05) were higher, whereas OC (3.6 +/- 2.4 vs 5.2 +/- 1.9 mg/l; p<0,05) was lower than in controls. In AC patients, GSU (34.9 +/- 5.3 vs 35.2 +/- 3.4%) did not differ significantly from controls, whereas OC (16.8 +/- 8.8 vs 6.9 +/- 2.9 microg/l; p<0.001) and U-DPD (30.9 +/- 13.6 vs 21.0 +/- 5.7 pmol/pmol; p<0.01) were higher. Stepwise multivariate linear regression analysis was performed with disease activity, creatinine clearance, age, and years since menopause as predictor variables and GSU or OC or U-DPD as dependent variables. The significant partial regression coefficients ( r) were: in TT, free triiodothyronine (fT3) with GSU ( r = 0.37; p<0.005), Ln OC ( r = 0.30; p = NS), Ln U-DPD ( r = 0.76; p<0.0001), respectively; in PHPT, PTH with GSU ( r = 0.74; p<0.001), Ln OC ( r = 0.50; p<0.05), Ln U-DPD ( r = 0.64; p<0.001); in CS Ln urinary free cortisol with OC ( r = -0.68; p<0.001) and U-DPD ( r = 0.66; p<0.05). Our data suggest that GSU could represent a valuable clinical tool for evaluating bone turnover rate in PHPT, CS, TT but not in AC. The behavior of GSU and OC and U-DPD is non-uniform in disorders characterized by a marked uncoupling between bone formation and resorption.